Вивчення розповсюдженості та можливостей оптимізації діагностики гестаційного діабету - Медведь, В. І.; Бичкова, Є. О.; Бикова, Л. М. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article presents data on the prevalence in the population of Ukrainian women for gestational diabetes received during four years of a screening test in pregnant women with subsequent confirmation of the diagnosis by conducting three-hour oral glucose tolerance test with a load of 100 g of glucose regulated by current legislation. Disadvantages of mentioned diagnostic algorithm are discussed and the possibilities of simplifying the diagnostic procedure with an analysis of the expected results of such changes are shown.